IMPLEMENTASI DIGITAL LIBRARY UNTUK PENINGKATAN LAYANAN PERPUSTAKAAN DI DINAS PERPUSTAKAAN UMUM DAN ARSIP DAERAH KOTA MALANG - Istigfareen, Firdausi (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Libraries as public organizations that provide information services to the general public by prioritizing user satisfaction are required to adapt to the times. This has an impact on the orientation of the library to improve the quality of library services. The urgency of a library that is not only a place to store information, but also creates and shares technology-based information is an opportunity to innovate in organizing information. The Malang City Public Library and Regional Archives Service innovates through collaboration with PT Gramedia and PT Digidio Nusantara to provide technology-based information services in the form of digital libraries. This research aims first; knowing how to manage digital library services, second; knowing how to apply digital library services to improve library services at the Malang City Public Library and Regional Archives Office. This study uses a descriptive qualitative method with a case study approach. The research data was obtained through observation, interviews, and documentation using triangulation data analysis. The result of this study is that digital library services at the Malang City Public Library and Regional Archives Service are managed in accordance with library management procedures in general, including planning activities that are then determined by strategic work plans, funding and budgeting activities stipulated in the Budget Needs Plan (RKA), development of digital collections that are tailored to user needs through user studies and collaboration with publishers, human resource management and monitoring and evaluation on a regular basis every year. This management activity is the basis for the implementation of effective and efficient digital library services through service development, socialization, and service accessibility in improving library services at the Malang City Public Library and Regional Archives Office.